PENGEMBANGAN INSTRUMEN TES DIAGNOSTIK TWO-TIER UNTUK MENGIDENTIFIKASI MISKONSEPSI SISWA SMP PADA POKOK BAHASAN KLASIFIKASI MATERI - Kurnia, Atika Fitri (2014)
Classification of matter is one of abstract topic and important basic matter that must be understood by students. Abstract contents has potential occurrence of misconceptions in students. Misconceptions can be a barrier for students to learn next concepts. Therefore, a diagnostic test is needed as a tool to identify students' misconceptions. Diagnostic test that used is two-tier diagnostic test. In addition, a minimum of development of the two-tier diagnostic test instrument in Indonesia make to development of the two-tier diagnostic test instrument is needed to identify junior high school students' misconceptions in classification of matter. The purpose of this research are to describe the development of two-tier diagnostic test instrument based on result data of essay test and multiple-choice test with free reason, produce two-tier diagnostic test instrument with good validity and reliability criteria, and to know junior high school students' misconceptions in classification of matter subject. The method of this result is research and development (R and D). Development two-tier diagnostic test instrument in this research through three phases, those are essay test, multiple choice test with free reason, and two-tier diagnostic test. Essay test and multiple-choice test with free reason obtained some misconceptions those are used to develop a two-tier diagnostic test instrument. Quality of two-tier test that develop was tested by validity test with content validity ratio (CVR) method and determining mean value and reliability test with Kuder-Richardson equation (KR # 20). There are valid 15 two-tier test with high reliability criteria, that is 0,66. Valid and reliable two-tier test was tested to 31 student, then analyzed to know students' misconceptions that occur those misconceptions can be use by teacher to prevent the occurrence of misconceptions again in junior high school students in classification of matter subject.